TIPE2 Suppresses Malignancy of Pancreatic Cancer Through Inhibiting TGFβ1 Mediated Signaling Pathway - Feng, Fang; Liu, Chunliang; Bian, Huahui; Cai, Wei; Zhou, Ying; Zhou, Li; Zhuang, Zhixiang (Frontiers in Oncology, 2021)
Pancreatic cancer is a major cause of cancer-related mortality for the difficulty in diagnosis, high metastasis and drug resistance. Therefore, understanding of the signal regulation of apoptosis, metastasis and tumor microenvironment could provide a target for treatment of pancreatic cancer. TIPE2 is an essential regulator of tumor apoptosis, inflammation and immune homeostasis. But it is unclearly about the role of TIPE2 in pancreatic cancer. In this study, we found the expression of TIPE2 was decreased in pancreatic cancer tissues compare to paracancerous tissues, which was negative correlated with tumor size in patients. Overexpression of TIPE2 in pancreatic cancer cell lines by lentiviral vector obviously suppressed cell proliferation, invasion, migration and increased cell apoptosis in vitro. Additionally, real time PCR and western blot analysis showed TIPE2 could inhibit the expression of MMPs and N-Cadherin, and increase the expression of Bax in pancreatic cancer cells. Similarly, TIPE2 could inhibit tumor growth in vivo, decrease the expression of Ki67 and N-Cadherin, and increase the expression of Bax by IHC analysis in tumor tissues isolated from tumor-bearing mice. Mechanistic studies exhibited that TIPE2 might suppress pancreatic cancer development through inhibiting PI3K/AKT and Raf/MEK/ERK signaling pathways triggered by TGFβ1. Moreover, the tumor-infiltrating lymphocytes from tumor-bearing mice were analyzed by flow cytometry, and TIPE2 could promote T cell and DC activation. Further study showed that TIPE2 could promote T cell activation to exert an anti-tumor effect possibly through activation of DCs in a TGFβ1 dependent manner. In general, we described the multiple regulatory mechanisms of TIPE2 in pancreatic tumorigenesis and tumor microenvironment, which suggested TIPE2 may be serves as a potential therapeutic target in pancreatic cancer.